Association between Cerebral Small Vessel Disease and Plasma Levels of LDL Holesterol and Homocysteine: Implications for Cognitive Function: LDL, Homocysteine, Small Vessel Disease, Cognitive Function Link - Cheng, Yan; Li, Lichao; Lv, Yafei; Zhang, Long; Chen, Wenhua; Xu, Gongda (Journal of Medical Biochemistry, 2024)
Background: Investigate the correlation between low-density lipoprotein (LDL) cholesterol, homocysteine and cognitive function in patients with cerebral small vessel disease (CSVD). Methods: 240 patients with CSVD confirmed by head MRI in the Department of Neurology from January 2020 to December 2023 were retrospectively included in the study. All the patients had complete blood biochemical examination, and their cognitive function was evaluated by Montreal Cognitive Assessment Scale (MoCA), and after correcting for the factor of years of education, the patients were divided into a group of normal cognition (MoCA ≥26, 70 patients) and a group of cognitive function (MoCA ≥26, 70 patients) according to the scores. After correcting for the factor of years of education, the patients were divided into the normal cognitive function group (70 cases with MoCA ≥26) and the cognitive dysfunction group (170 cases with MoCA